Policies and Legislation Concerning the Establishment of Higher Education Institutions Funded Through Waqf: Study in Malaysia and Indonesia: (Polisi dan Perundangan Penubuhan Institusi Pendidikan Tinggi Berasaskan Wakaf: Kajian di Malaysia dan Indonesia) (Kanun: Jurnal Undang-undang Malaysia, 2019)
A country's development is closely related to the development of its Higher Education Institutions (HEI). The success and continued existence of the influences of the Ottoman caliphate has shown that the waqf-funded educational system has had a positive impact in Turkey. This system has also been adopted in many countries, including Malaysia and Indonesia. The main objective of this study is to analyse the legislation and the procedures involved in the establishment of the waqf-funded HEI. This study was conducted using qualitative methods involving universities in Malaysia and Indonesia as case studies. Semi-structured interviews were used for data collection, supported by references to applicable policies and related legal documents. The findings of this study show that there are as yet no specific policies concerning the establishment of waqf-funded HEIs in both countries. Waqf-funded HEIs in Malaysia are established under the University and University Colleges Act 1971 and related regulations concerning waqf and state Islamic religious administration, while in Indonesia they are mostly private insitutions established through foundations.Keywords: higher education institutions, waqf, policies, legislation.